Dissimilarity and Horizon of Expectation: A Reading in a Pre-Islamic Text - Ziadi, Abdelaaziz; Charef , Abdelkarim (LANGUAGE ART, 2025)
This paper aims to approach a model of ancient Arab criticism by employing concepts from German reception theory, as represented by Hans Robert Jauss and Wolfgang Iser. This approach highlights the creative features of Nabigha Al-Dhubyani's Reception of Hassan ibn Thabit's poetry and their differences in the famous recitation incident. In an attempt to explore specific reception processes and their utilization, these processes include "conjoint reading," which Iser stimulates through "indeterminacy" and "the horizon of expectation" between the text and the contemporary receiver of the work, as well as the impact of the first reception in the series of subsequent receptions or "the merging of horizons," as Jauss would put it.